Comparative Study of Two Commercial Photovoltaic Panels under Natural Sunlight Conditions - Daniel T. Cotfas; Petru A. Cotfas (International Journal of Photoenergy)
Photovoltaic (PV) panels are used for both standalone applications and grid-connected systems. In the former case, the PV panels used vary in size, from very small, for smart solar garden lamps, to standard, in order to ensure the necessary electric energy for a house. For these cases, it is very important to choose the best solution in terms of photovoltaic cell materials. In this paper, a comparative study of two commercial photovoltaic panels, monocrystalline and amorphous silicon, is presented. The two photovoltaic panels are measured in natural conditions, during two years, in Brasov, Romania. The emphasis is placed upon the maximum power generated by the two panels, but the cost and the lifetime are also taken into consideration. The gain in average maximum power for the monocrystalline silicon panel varies from 1.9 times for low irradiance to 2.4 times higher than the one obtained from the amorphous silicon panel, during the test period. The temperature of the monocrystalline silicon panels is lower than that of the amorphous silicon panel in the majority of measurements. The degradation rate determined in two years is 1.02% for the monocrystalline silicon panel and 1.97% for the amorphous silicon panel.